Surgical and Pathological Characteristics of Papillary Thyroid Cancer in Children and Adolescents - Davor Dzepina (International Journal of Pediatrics)
Background. Thyroid carcinoma is a relatively rare pediatric pathology, comprising around 3% of all childhood tumors. We investigated parameters of tumor aggressiveness, multicentricity, and locoregional metastatic spread patterns in patients up to 18 years of age and made comparison with the older group. All patients were operated upon with total thyroidectomy, with or without lymph-node neck dissection. Results. Patients with papillary carcinoma present with more advanced stage, larger primary tumor, and more commonly present with palpable thyroid and/or neck node. Overall, papillary cancer demonstrated pathological aggressiveness as defined by our criteria in 60%, multicentricity in 40%, and locoregional metastatic foci in 77% of cases. Multicentric tumor foci in both thyroid lobes and tumor aggressiveness were identified as a risk factor for metastatic development. Conclusion. By observing clinicopathological parameters, we demonstrated that papillary thyroid cancer behaves more aggressively in the younger group. We recommend total thyroidectomy with careful intraoperative exploration of thyroid bed and lateral neck in search for possible metastatic spread. In case of positive findings, it is obligatory to perform a standard neck dissection, keeping in mind that neck lymphonodes are primary site of locoregional recurrence. With meticulous attention to technical aspects of operation, perioperative morbidity should be minimal.